Molecular magnetic resonance imaging of brain–immune interactions - Gauberti, Maxime; Montagne, Axel; Quenault, Aurélien; Vivien, Denis (Frontiers in Cellular Neuroscience, 2014)
Although the blood-brain barrier (BBB) was thought to protect the brain from the effects of the immune system, immune cells can nevertheless migrate from the blood to the brain, either as a cause or as a consequence of central nervous system (CNS) diseases, thus contributing to their evolution and outcome. Accordingly, as the interface between the CNS and the peripheral immune system, the BBB is critical during neuroinflammatory processes. In particular, endothelial cells are involved in the brain response to systemic or local inflammatory stimuli by regulating the cellular movement between the circulation and the brain parenchyma. While neuropathological conditions differ in etiology and in the way in which the inflammatory response is mounted and resolved, cellular mechanisms of neuroinflammation are probably similar. Accordingly, neuroinflammation is a hallmark and a decisive player of many CNS diseases. Thus, molecular magnetic resonance imaging (MRI) of inflammatory processes is a central theme of research in several neurological disorders focusing on a set of molecules expressed by endothelial cells, such as adhesion molecules (VCAM-1, ICAM-1, P-Selectin, E-Selectin, …), which emerge as therapeutic targets and biomarkers for neurological diseases. In this review, we will present the most recent advances in the field of preclinical molecular MRI. Moreover, we will discuss the possible translation of molecular MRI to the clinical setting with a particular emphasis on myeloperoxidase imaging (MPO), autologous cell tracking and targeted iron oxide particles (USPIO, MPIO).